Distigmasterol-Modified Acylglycerols as New Structured Lipids—Synthesis, Identification and Cytotoxicity - Magdalena Rudzińska (MDPI AG, 2021)
Plant sterols, also referred as phytosterols, have been known as bioactive compounds which have cholesterol-lowering properties in human blood. It has been established that a diet rich in plant sterols or their esters alleviates cardiovascular diseases (CVD), and also may inhibit breast, colon and lung carcinogenesis. Phytosterols, in their free and esterified forms, are prone to thermo-oxidative degradation, where time and temperature affect the level of degradation. Looking for new derivatives of phytosterols with high thermo-oxidative stability for application in foods, our idea was to obtain novel structured acylglycerols in which two fatty acid parts are replaced by stigmasterol residues. In this work, asymmetric (1,2- and 2,3-) distigmasterol-modified acylglycerols (dStigMAs) were synthesized by the covalent attachment of stigmasterol residues to sn-1 and sn-2 or sn-2 and sn-3 positions of 3-palmitoyl-sn-glycerol or 1-oleoyl-sn-glycerol, respectively, using a succinate or carbonate linker. The chemical structures of the synthesized compounds were identified by NMR, HR-MS, and IR data. Moreover, the cytotoxicity of the obtained compounds was determined. The dStigMAs possessing a carbonate linker showed potent cytotoxicity to cells isolated from the small intestine and colon epithelium and liver, whereas the opposite results were obtained for compounds containing a succinate linker.